Literasi Keuangan dan Pendapatan terhadap Keputusan Investasi Mahasiswa dengan Perilaku Keuangan sebagai Variabel Intervening - Khofifah Amalia Sekar Putri; Sari Andayani (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of financial literacy, income, and financial behavior as intervening variables on investment decisions of active undergraduate students of accounting at UPN "Veteran" East Java. The population in this study were active students majoring in accounting at UPN "Veteran" East Java who had worked or were self-employed. The research method used is a quantitative method. The data collection method was carried out using a questionnaire in the form of a Google form. The analysis technique used is Partial Least Squares (PLS) with the help of SmartPLS 3.0 software. The results showed that financial literacy and financial behavior had a positive and significant effect on investment decisions, while income had no effect on investment decisions. Financial literacy has a positive and significant effect on financial behavior while income has no effect on financial behavior. In addition, the mediation test results show that financial behavior mediates the relationship between financial literacy and investment decisions and does not mediate the relationship between income and investment decisions. Keywords: Investment Decision, Financial Literacy, Income, Financial Behavior